John Lanchester's Capital: financial risk and its counterpoints. Issue 3 (16th April 2017) - Korte, Barbara
ABSTRACT: John Lanchester's Capital (2012) reads London as a space in which risk and chance are complexly entangled – for 'native' Londoners as well as people who come to it from all parts of the world and for various reasons: as businessmen, economic migrants, political refugees or talent from the Global South. Capital comes across as a 'social novel' in the nineteenth-century sense: as a panorama of social types and narrative trajectories. It is precisely this conventional mode of presentation (and its tradition of social critique) that enables Lanchester's novel to trace what risk, with both its positive and negative implications, means for the various characters whose lives before and after the 2008 crash it follows. Capital thus exposes reckless capitalism but also explores many other meanings that risk and risk-taking can have in globalised urban settings of the twenty-first century. It personalises and humanises 'risk', and it demands an ethical positioning of the readers as it juxtaposes the irresponsible risk-taking of the finance world with the risk-taking and resilience of individual people who find themselves in different forms of precarious life.